Analysis of Factors Relating To Tourists Visiting Interest In Suban Hot Spring Tourist Destinations Curup City - Sindi Oktapiani; Heni Nopianti; Diyas Widiyarti (Dinasti International Journal of Education Management And Social Science, 2024)
The research was motivated by the researcher's interest in tourism in the city of Curup, especially the hot spring suban tourist destination. Various natural resources in Curup City such as mountains, hills, lakes, or waterfalls, and others have the potential to become tourist attractions that attract tourists to visit. Suban Air Panas is a tourist attractionmanaged by the Rejang Lebong Regency Culture and Tourism Office. Suban Air Panas is one of the mainstay attractions of Curup City which is the main destination for visitors on holidays and weekdays. The research uses George C. Homans' Social Exchange Theory as the foundation for analysis to investigate the elements that are associated with tourists' interest in visiting tourist spots in the city of Curup. This study used a quantitative research approach for its research. Information was acquired through literature study, documentation, questionnaires, observation, and secondary data. Informants were selected using the purposive sampling technique and accidental sampling method from visitors to Suban Hot Springs tourist attraction. The analysis model used is multiple linear regression, with tourist attraction, facilities, and accessibility as independent variables, and tourist interest as the that is dependant. The research results show that the three independent variables significantly influence tourists' interest in traveling. This indicates that these variables play a major role in attracting tourists. Therefore, the tourism industry must pay attention to these variables if they wish to increase their contribution to Regional Original Revenue (PAD).